Improving Mechanical Properties of Biofoam Using Oil Palm Fiber as Filler at Various Temperatures and Processing Times - Feri Rahmadani; Isna Syauqiah; Agung Nugroho (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Biofoam, as an alternative packaging material based on tapioca starch, has become a choice for environmentally friendly packaging. However, biofoam has a drawback in terms of weak mechanical properties. The use of oil palm fiber, a by-product of CPO production, has gained interest as a material that can improve the mechanical properties of biofoam. This study aims to produce biofoam with the best mechanical characteristics as packaging material through variations in temperature and processing time. The production of biofoam was carried out using the thermopressing method on tray-shaped molds with variations in molding temperature of 180°C, 190°C, and 200°C for 180 seconds and 210 seconds. The dough formulation consisted of 80% starch, 20% fiber, with the addition of 25 grams of water. Mechanical property testing was conducted through tests for moisture content, water adsorption, biodegradability, compressive strength, and tensile strength. The variation of 190°C temperature and 210 seconds baking time resulted in biofoam with the best mechanical properties. This biofoam showed the highest compressive strength value of 26.94 kPa, tensile strength test of 83.11 kPa, the second-highest biodegradability with a percentage of 78.93%, and the second-lowest moisture content with a value of 7.56%. These results indicate that biofoam at a molding temperature of 190°C and a baking time of 210 seconds has the best mechanical properties, making it superior as an environmentally friendly alternative packaging material compared to other formulations. Keywords: Biofoam, Oil palm fiber, Temperature, Thermopressing.